A morphological and phylogenetic analysis of Ornithodoros marinkellei (Acari: Argasidae), with additional notes on habitat and host usage - Venzal, José Manuel (2018)
Ornithodoros marinkellei was described from larvae collected on Pteronotus spp. bats in Colombia and Panama. More recently, this tick was reported in the Brazilian Amazon. Because some morphometric differences were observed between O. marinkellei larvae from Colombia and Brazil, it was proposed that further investigations were needed to assess whether the differences could be attributed to intra- or inter-specific polymorphism. Herein, we collected O. marinkellei specimens in the type locality of Colombia, in Brazil, and in a new locality in Nicaragua, expanding the distribution of the species to Nicaragua. Morphometric analysis of larvae and adults, corroborated by a principal component analysis (PCA), indicated that the Brazilian specimens were larger than specimens from Colombia and Nicaragua. Phylogenetic analysis inferred from the mitochondrial 16S rRNA gene showed ticks from Colombia and Nicaragua more genetically related than any of them with ticks from Brazil, although ticks from the three countries grouped in a clade sister to a major clade containing sequences of various Neotropical Ornithodoros species. We concluded that ticks identified as O. marinkellei from Colombia, Nicaragua, and Brazil represent the same taxon, and that the genetic and morphological differences between them are likely to have a geographical bias. We redescribed the nymph of O. marinkellei, which has a vestigial hypostome, probably incompatible with blood feeding. We also report human infestation by O. marinkellei adults. As all reports of O. marinkellei adults have been from hot caves (temperature > 35 °C), this abiotic condition could be a limiting factor for the occurrence of this tick species.